2019
DOI: 10.1038/s41467-019-11094-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of recombinant human CCR4-NOT reveals molecular insights into regulated deadenylation

Abstract: CCR4-NOT is a conserved multiprotein complex which regulates eukaryotic gene expression principally via shortening of poly(A) tails of messenger RNA or deadenylation. Here, we reconstitute a complete, recombinant human CCR4-NOT complex. Our reconstitution strategy permits strict compositional control to test mechanistic hypotheses with purified component variants. CCR4-NOT is more active and selective for poly(A) than the isolated exonucleases, CCR4a and CAF1, which have distinct deadenylation profiles in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 59 publications
6
90
0
Order By: Relevance
“…A similar observation was reported in a previous study [26]. It is possible that CNOT6/6L might be able to function independently of the complex to deadenylate mRNAs, because purified CNOT6/6L and CNOT7/8 exhibit deadenylase activity in vitro [17,39,40]. It would be intriguing to examine whether there are any biological contexts where CNOT6/6L function independently in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…A similar observation was reported in a previous study [26]. It is possible that CNOT6/6L might be able to function independently of the complex to deadenylate mRNAs, because purified CNOT6/6L and CNOT7/8 exhibit deadenylase activity in vitro [17,39,40]. It would be intriguing to examine whether there are any biological contexts where CNOT6/6L function independently in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Purified human CCR4-NOT complex (50 µg) was then added to the beads. The reconstitution of the human CCR4-NOT complex was described elsewhere (57) and includes the following eight components: CNOT1 (amino acids 1-2376), CNOT2 (1-540), CNOT3 (1-753), CNOT10 (25-707), CNOT11 (257-498), CAF1 (1-285), CCR4a (1-558), CAF40 (1-299). After 1 hour incubation, the beads were washed three times with binding buffer and the proteins were eluted with binding buffer supplemented with 2.5 mM D-desthiobiotin.…”
Section: Methodsmentioning
confidence: 99%
“…CNOT9 has been proposed to play regulatory roles within the complex in a manner that assists mRNA decay by interacting with CNOT1 and stimulating catalysis by subunits CNOT6, CNOT6L, CNOT7 and CNOT8 (Pavanello et al, 2018).This idea was further perpetuated by an in-vitro study of the human CCR4-NOT complex, which suggested that stimulus-dependent CNOT9 interaction with RNA binding proteins results in targeted mRNA decay (Raisch et al, 2019). In congruity with this idea we observed a similar trend within our RNA-Seq data.…”
Section: Discussionmentioning
confidence: 99%